Endophytic Microorganisms From the Tropics as Biofactories for the Synthesis of Metal-Based Nanoparticles: Healthcare Applications - Bogas, Andréa Cristina; Henrique Rodrigues, Saulo; Gonçalves, Mariana Ottaiano; De Assis, Marcelo; Longo, Elson; Paiva De Sousa, Cristina (Frontiers in Nanotechnology, 2022)
Nanoparticles (NPs) have gained great attention in recent years due to their extensive and innovative applications in medicine. However, conventional physicochemical approaches for the synthesis of NPs may be limited and costly, and the reaction by-products are potentially toxic for human health and the environment. Bio-mediated synthesis of NPs exploiting microorganisms as nanofactories has emerged as an alternative to traditional methods, as it provides economic and environmental benefits. Tropical ecosystems harbor a high diversity of endophytes, which have a diverse array of metabolic pathways that confer habitat adaptation and survival and that can be used to produce novel bioactive compounds with a variety of biological properties. Endophytic bacteria and fungi cultivated under optimum conditions have potential for use in biogenic synthesis of NPs with different characteristics and desired activities for medical applications, such as antimicrobial, antitumoral, antioxidant and anti-inflammatory properties. The bio-mediated synthesis of metal-based NPs can be favored because endophytic microorganisms may tolerate and/or adsorb metals and produce enzymes used as reducing agents. To our knowledge, this is the first review that brings together exclusively current research highlighting on the potential of endophytic bacteria and fungi isolated from native plants or adapted to tropical ecosystems and tropical macroalgae as nanofactories for the synthesis of NPs of silver, gold, copper, iron, zinc and other most studied metals, in addition to showing their potential use in human health.